Hukum Internasional Sebagai Sumber Hukum Dalam Hukum Nasional - Rosdiyanti, Evi; Abustan, Abustam (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2020)
Countries agreement contained in an international agreement in the form of bilateral agreements, regional and multilateral agreements that are binding on the parties and a law for that entered into an agreement (pacta sunt servanda). International agreements that have been agreed and validated in a ratification by a country, then the agreement is valid and binding upon all be a source of law for the enforcement of law in making decisions. This is true also in Indonesia. Any international agreement that has been followed by Indonesia, which is contained in a ratification requirement or not, still have the force of binding for both parties.